Parenthood as a driver of increased gender inequality during COVID-19? Exploratory evidence from Germany - Lena Hipp; Mareike Bünning (European Societies, 2021)
Drawing on three waves of survey data from a non-probability sample from Germany, this paper examines two opposing expectations about the pandemic's impacts on gender equality: The optimistic view suggests that gender equality has increased, as essential workers in Germany have been predominantly female and as fathers have had more time for childcare. The pessimistic view posits that lockdowns have also negatively affected women's jobs and that mothers had to shoulder the additional care responsibilities. Overall, our exploratory analyses provide more evidence supporting the latter view. Parents were more likely than non-parents to work fewer hours during the pandemic than before, and mothers were more likely than fathers to work fewer hours once lockdowns were lifted. Moreover, even though parents tended to divide childcare more evenly, at least temporarily, mothers still shouldered more childcare work than fathers. The division of housework remained largely unchanged. It is therefore unsurprising that women, in particular mothers, reported lower satisfaction during the observation period. Essential workers experienced fewer changes in their working lives than respondents in other occupations.
doi:10.7802/2042
Keywords: 300; COVID-19; gender; family; employment; division of labour; satisfaction